Effective and ineffective academic writing support for ESL students: A higher education perspective - Mohale, Ntshimane Elphas (Journal of Research on English and Language Learning (J-REaLL), 2025)
Academic writing presents significant challenges for students who use English as a second language, often affecting students’ academic performance and progress. Given its critical role in academic success, various institutions have introduced various support approaches to enhance students’ writing skills. However, ongoing challenges suggest that these approaches vary in effectiveness. This study explored the effective and ineffective academic writing support approaches. Employing a literature review analysis, questionnaire, and interview, the study collected data within the framework of transactional distance theory. Findings indicate that scaffolded writing support is a highly effective pedagogical approach, as it systematically deconstructs the writing process into manageable steps. Other effective approaches include explicit and timely feedback, tailored writing instruction, simplified academic language, structured peer-review sessions, and enhanced accessibility to writing resources. In contrast, ineffective approaches involved the use of complex academic language, text-heavy materials, information overload, limited engagement time, and a lack of practical exercises, all of which hinder students’ ability to internalize key writing concepts. Additional challenges include language barriers, vague feedback, and unstructured peer-review sessions. The study contributes to the refinement of curriculum design, academic writing support approaches, and English as a Second Language support structures by promoting feedback-driven and student-centered interventions that align with students’ needs, ultimately improving writing outcomes, enhancing retention rates, and reducing failure rates. Overcoming academic writing challenges and reducing transactional distance is at the core of effective student support approaches.